Crossroads of freedom : Antietam - McPherson, James M. (Oxford ; New York : Oxford University Press, 2002)
In this book, prize winning author James M. McPherson tells the story of the battle of Antietam - the turning point of the whole Civil War, and the bloodiest day in American history. In a concise narrative, McPherson takes readers through the events leading up to Antietam, and through the savage fighting of the battle itself. The final chapters will discuss the aftermath of the battle and why it truly was a pivotal moment in American history.
Introduction: death in September -- The pendulum of war, 1861-1862 -- Taking off the kid gloves, June-July 1862 -- "The federals got a very complete smashing", August-September 1862 -- Showdown at Sharpsburg -- The beginning of the end.
Includes bibliographical references (p. [185]-190) and index.
Keywords: Antietam, Battle of, Md., 1862.; United States -- History -- Civil War, 1861-1865 -- Battles -- Maryland -- Antietam; Amerikaanse burgeroorlog; Geschichte; Antietam Creek -- Schlacht